The Implementation of Joyful Learning Strategies Using Experimental and Project Methods in terms of Students’ Creativity and Self-Discipline - Anggraeni, Melyana Dyah; Sunarno, Widha; Suparmi, Suparmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to analyze the difference of students’ study result between the joyful learning strategics using the experimental and project method seen from the creativity and self-discipline. The research method used in this study was the experimental method. The research design used in the study was a quasi-experimental research design. The sample was obtained by using the Cluster Sampling technique which consisted of two classes through scientific-based learning observations using project and experimental methods in different classes. The data collection on the learning outcomes of the knowledge aspect used to test techniques, the attitude aspect used the questionnaire technique, and the skill aspect used the observation sheet. The results of this study shows that project method influencing students’ study and skill result better than the experimental method. The learning outcomes of students’ knowledge and skills with creativity were better than those of students with low creativity. The learning outcomes of students with high self-discipline were better than those of students with low self-discipline.